PROBLEM SOLVING ABILITY OF STUDENTS WITH COGNITIVE IMPULSION STYLE BASED ON SOLO TAXONOMY - Appulembang, Oce Datu; Tamba, Kimura Patar (Universitas Papua, 2021)
The problem-solving ability between reflective and impulsive subjects from several studies shows that reflective subjects are always superior than impulsive subjects. The purpose of this study was to identificate and to describe students' problem-solving abilities with impulsive cognitive style in solving superitem test problems and their characteristics. This research is a qualitative descriptive study. The data collection techniques used were the MFFT test, the superitem test, and interviews. Based on the results of the superitem test, it shows that the two impulsive subjects have differences in achieving the level of problem-solving ability thinking. Impulsive-01 subjects can reach all thinking levels based on SOLO taxonomy while impulsive-02 subjects can only solve problems at the unistructural level. Although the research shows that the impulsive-01 subject has the characteristics of being fast, less accurate, less thorough, and seeming rushed in solving problems, the subject can finish up to the extended abstract level. The impulsive-02 is able to connect by making assumptions in solving the problem, it's just that the inability to solve this problem due to not understand the problem.